Realizing p‐Type and n‐Type Doping of a Single Conjugated Polymer via Incorporation of a Thienoisatin‐Terminated Quinoidal Unit - Geng, Xiaokang; Du, Tian; Xu, Chenhui; Liu, Yingying; Deng, Yunfeng; Geng, Yanhou (Advanced functional materials, 2023)
Selective doping of a single conjugated polymer (CP) to obtain p‐type and n‐type conductive materials would be highly attractive for organic thermoelectric applications, because it will greatly reduce the time and costs of synthesizing different types of CPs. However, this strategy has rarely been investigated. In this study, two CPs are synthesized, designated PTQDPP‐T and PTQDPP‐2FT, based on a newly developed quinoidal unit with thienoisatin as the termini and a thiophene‐flanked diketopyrrolopyrrole (ThDPP) unit as the quinoidal core. The electron‐rich thiophene rings in thienoisatin and the electron delocalization induced by thienoisatin resulted in polymers with high‐lying highest occupied molecular orbital, and the electron‐deficient nature of ThDPP unit and its quinoidal backbone endowed the polymers with low‐lying lowest unoccupied molecular orbitals. As a result, both polymers can be p‐type and n‐type doped. Because of its high mobility, doped PTQDPP‐2FT performed better in organic thermoelectric devices than the doped PTQDPP‐T. After being doped with FeCl3 and N‐DMBI, PTQDPP‐2FT showed p‐type and n‐type power factors of 278.2 and 2.37 µW m−1 K−2, respectively. These are the best for bipolar (p‐type and n‐type) performances that obtained by selective doping of a single polymer. Polymers that can be both p‐doped and n‐doped are synthesized via incorporating a thienoisatin terminated quinoidal unit. Organic thermoelectric devices with a p‐type power factor >270 µW m−1 K−2 and an n‐type power factor >2 µW m−1 K−1 are fabricated by selective doping the polymers with FeCl3 and N‐DMBI, respectively.